Philosophical perspectives on teacher education - Heilbronn, Ruth; Foreman-Peck, Lorraine; Biesta, Gert. (Chichester, West Sussex, UK ; Malden, MA : Wiley Blackwell, 2015)
'Philosophical Perspectives on Teacher Education presents a series of well-argued, thought-provoking essays that point to the ethical considerations that should be addressed when proposing and implementing teacher training and educational policies and practices'--
Ethical Deliberation: What is it? -- Facilitating Ethical Deliberation -- Methodology and Methods -- Data Presentation, Analysis and Discussion -- Conclusions and Recommendations -- Part 3 Being a Teacher? -- Chapter 7 The Role of Higher Education in Teacher Education: A Reorientation Towards Ontology -- Introduction -- The Ontological Turn in Higher Education -- The Dialogic Event of Teacher Education -- Implications for The Being of Students and Teacher Educators in Higher Education -- Chapter 8 Cultivating Human Capabilities in Venturesome Learning Environments -- Introduction -- Venturesome Learning Environments and Their Domains of Relations -- The Possible and The Practical: Research on Learning Environments in a Policy Context -- Conclusion -- Chapter 9 Towards a Theory of Well-Being for Teachers -- Introduction -- What is Meant by'Well-Being'? -- Challenges to Teachers' Well-Being -- What are The Elements of Well-Being for Teachers? -- Developing Self-Knowledge -- Reflection -- Well-Being and Professional Development -- Conclusion -- Note -- References -- Index -- EULA.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Teachers -- Training of -- Philosophy; Electronic books